Pendampingan Perajin Tempe Desa Sulang Kabupaten Rembang untuk Meningkatkan Penjualan Menggunakan Labeling dan Internet Marketing - Angga Debby Frayudha (LPPM Universitas Yudharta Pasuruan, 2020)
The purpose of writing this PKM report is to provide input regarding the strategic assistance for the business development of tempe craftsmen located in Sulang Village, Sulang District. The background that underlies this PKM is that tempe craftsmen in Sulang Village do not have a business identity and still have not implemented internet social media as a marketing medium. The selection factor for this mentoring strategy was carried out because there were many business competitors producing tempe in Rembang Regency and tempe craftsmen in Sulang Village who wanted to distribute tempe products in other districts or in other districts using labels and social media. making labels on packaging which aims to facilitate consumers in recognizing tempe products. The author examines the development strategies used by this business with sources from books and journals related to the title of this final report. In writing this report the authors used the service learning method, namely: the preparation stage, the service stage, the reflection stage. After reviewing the methods and reference sources, the recommended development strategies for tempe craftsmen include business identity (label), making SIUP, and internet marketing (whatsapp).